Long-term impacts of climate change on coastal and transitional eco-systems in India: an overview of its current status, future projections, solutions, and policies. Issue 18 (19th April 2023) - Subramanian, Aishwarya; Nagarajan, Aditya Mosur; Vinod, Sruthi; Chakraborty, Samarshi; Sivagami, Krishanasamy; Theodore, Thomas; Sathyanarayanan, Sri Shalini; Tamizhdurai, Perumal; Mangesh, V. L.
Abstract : Urbanization and industrial development are increasing rapidly. Abstract : Urbanization and industrial development are increasing rapidly. These are accompanied by problems of population explosion, encroachment of agricultural, and construction lands, increased waste generation, effluent release, and escalated concentrations of several greenhouse gases (GHGs) and pollutants in the atmosphere. This has led to wide-scale adverse impacts. Visible effects are fluctuations in temperatures and precipitation, rising sea levels, unpredictable floods, storms and cyclones, and disruption to coastal and transitional ecosystems. In a country like India with a massive population of nearly 1.4 billion and around 420 million people dwelling on or near the coasts, this effect is pre-dominant. India has extensive coastlines on both sides that are subject to greater contact and high impact from the water bodies. The factors impacting climate change, its consequences, and future predictions must be analyzed immediately for implementing precautionary measures to ameliorate the detrimental effects. Several endemic species have been endangered as these changes have resulted in the loss of habitat and interfered with the food webs. Climatic impacts on transitional ecosystems also need to be considered to preserve the diversity of each. The cooperation of governmental, independent organizations and policymakers throughout the world is essential to control and mediate the impacts on health, agriculture, and other related sectors, the details of which have been elaborated in this review. The review analyses the trends in climatic variation with time and discusses a few extremities which have left permanent effects on the population primarily concerning the coastal – Indian scenario and its eco-systems.